STRENGTHENING FAMILY BUSINESS IN THE MUHAMMADIYAH TO IMPROVE THE POWER OF MOSLEM COMMUNITY FACING ASEAN COMMUNITY 2015 - Wahjono, Sentot Imam (2012)
Asean Community 2015 mandates a single market and production base shall comprise 5 core elements: 1) free flow of goods; 2) free flow of services; 3) free flow of investment; 4) free flow of capital; and 5) free flow of skilled labour. In addition, the single market and production base also include two important components, namely, the priority integration sectors, and food, agriculture and forestry. The family business in Muhammadiyah need to strengthen to increase the power of the moslem community encounter to ASEAN Community 2015. Considering the five basic elements and the two major component in the ASEAN single and production market is not a power of Muhammadiyah community yet. Meanwhile, the strength of Muhammadiyah business lies in the family business of Muhammadiyah members. One of the ways of strengthening the family business in the Muhammadiyah is to maintain business continuity by keeping the business leadership succession running smooth.